Prototype of smart parking system for Bukittinggi city parking buildings based on Arduino - Dwi Yonil, Roland; Hastuti; Dewi, Citra; Sardi, Juli (Journal of Industrial Automation and Electrical Engineering, 2024)
The parking system currently used in the Bukittinggi City parking building is not effective in managing parking, because it does not provide real-time information about the availability of parking spaces. As a result, use of parking spaces is often suboptimal, with some parking spaces remaining empty while others are full. This research aims to develop and test a system that is able to manage parking availability in real-time to maximize the use of existing space. Test results show that this system functions well and provides accurate results, which is very much needed in a tourist city like Bukittinggi. Overall, this system offers an efficient and practical solution to overcome parking challenges in big cities, and has the potential for further development, including integration with automatic payment systems and the use of more sophisticated sensors. This research shows that the Arduino-based Smart Parking system Uno in the Bukittinggi City parking building has succeeded in increasing the efficiency of parking space management. By using components such as push buttons, thermal printers, servo motors, limit switches, and LCD I2C displays, this system provides real-time information about parking availability, making it easier for motorists to find parking spaces quickly